Naplňování etických zásad při poskytování sociálních služeb - Sládek, Miloš (Univerzita Pardubice, 2009)
Social reality is so complex that in most cases social workers lack the essential degree of confidence in the decision-making process. When applying procedures in social services one has to ensure that not only is their activity sufficient from the professional point of view but also that their decision-making processes and behaviour are ethical. Social services reform have modified the fundamental activities of social workers which are the core of social services. Quality standards of social services emphasize some of the ethical topics and thoroughly impose on the provider of social services to process them in writing.
Keywords: social services; quality standard; ethics; provider; user